Clinical Evaluation of an Auto-Segmentation Tool for Spine SBRT Treatment - Chen, Yingxuan; Vinogradskiy, Yevgeniy; Yu, Yan; Shi, Wenyin; Liu, Haisong (Frontiers in Oncology, 2022)
Purpose: Spine SBRT target delineation is time-consuming due to the complex bone structure. Recently, Elements SmartBrush Spine (ESS) was developed by Brainlab to automatically generate a clinical target volume (CTV) based on gross tumor volume (GTV). The aim of this project is to evaluate the accuracy and efficiency of ESS auto-segmentation. Methods: 20 spine SBRT patients with 21 target sites treated at our institution were used for this retrospective comparison study. Planning CT/MRI images and physician-drawn GTVs were inputs for ESS. ESS can automatically segment the vertebra, split the vertebra into 6 sectors, and generate a CTV based on the GTV location, according to the International Spine Radiosurgery Consortium (ISRC) Consensus guidelines. The auto-segmented CTV can be edited by including/excluding sectors of the vertebra, if necessary. The ESS generated CTV contour was then compared to the clinically-used CTV using qualitative and quantitative methods. The CTV contours were compared using visual assessment by the clinicians, relative volume differences (RVD), distance of center of mass (DCM) and two other common contour similarity measurements such as dice similarity coefficient (DICE) and Hausdorff distance (HD). Results: Qualitatively, the study showed that ESS can segment vertebra more accurately and consistently than humans at normal curvature conditions. The accuracy of CTV delineation can be improved significantly if the auto-segmentation is used as the first step. Conversely, ESS may mistakenly split or join different spine columns when large curvatures in anatomy exist. In this study, human interactions were needed in 7 of 21 cases to generate the final CTVs by including/excluding sectors of the vertebra. In 90% of cases, the RVD were within ±15%. The RVD, DCM, DICE, and HD for the 21 cases were 3%±12%, 1.9±1.5 mm, 0.86±0.06, and 14.8±4.2 mm, respectively. Conclusion: ESS can auto-segment a CTV quickly and accurately and has a good agreement with clinically-used CTV. Inter-person variation and contouring time can be reduced with ESS. Physician editing is needed for some occasions. Our study supports the idea of using ESS as the first step for spine SBRT target delineation to improve the contouring consistency as well as to reduce the contouring time.